Nutraceuticals in the Prevention and Therapeutic Treatment of Cardiovascular and Cerebrovascular Disease. Issue 3 (19th May 2023) - Fleenor, Bradley S.; Carlini, Nicholas A.; Martens, Christopher R.
Abstract : Higher cardiovascular and cerebrovascular disease risk with aging is associated with stiffening of the large elastic arteries. Lifestyle interventions, including nutraceuticals, are a first-line defense to lower arterial stiffness. This review overviews the emerging cardioprotective effects of nutraceuticals to lower arterial stiffness and future cardiovascular and cerebrovascular disease risk. Abstract : Purpose: This review overviews and highlights arterial stiffening as a key physiological process and target for the prevention and/or lowering of cardio- and cerebrovascular disease (collectively CVD) risk. Methods: We identified nutraceutical approaches from randomized controlled trials and discussed the associated mechanisms by which these compounds lower age-related arterial stiffness. Age-related CVD are the leading cause of mortality in modernized societies. Arterial dysfunction, specifically stiffening of the large elastic arteries during midlife, is a key physiological process resulting in increased CVD risk. Current pharmaceutical approaches for lowering age-related arterial stiffness have limited efficacy, thus highlighting the need to identify novel approaches for lowering arterial stiffness and thereby CVD risk. Lifestyle interventions are a historical first-line approach to prevent and/or lower the adverse arterial stiffening effects observed with aging. Nutraceutical interventions, defined as a food or part of a food providing health benefits, are a nonpharmacological, novel lifestyle approach to lower age-associated arterial stiffness. Therefore, identifying nutraceutical approaches to lower CVD risk is clinically significant. Summary: This review provides a basic, yet essential, understanding for emerging nutraceutical strategies for the prevention and therapeutic treatment of CVD.